2015
DOI: 10.1016/j.jebo.2014.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Competitive in the lab, successful in the field?

Abstract: SNF SAMFUNNS-OG NAERINGSLIVSFORSKNING AS-er et selskap i NHH-miljøet med oppgave å initiere, organisere og utføre eksternfinansiert forskning. Norges Handelshøyskole og Stiftelsen SNF er aksjonaerer. Virksomheten drives med basis i egen stab og fagmiljøene ved NHH.SNF er ett av Norges ledende forsk ningsmiljø innen anvendt økonomisk-administrativ forskning, og har gode samarbeidsrelasjoner til andre forskningsmiljøer i Norge og utlandet. SNF utfører forskning og forsknings baserte utredninger for sentrale besl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 32 publications
3
52
0
Order By: Relevance
“…This approach was taken in Berge et al (2014); they find that females have weaker results from receiving capital and training, and that women were less competitive at endline. In associated work, the authors find that competitiveness as measured in their game does predict business success (Berge et al, 2015). Further research on this is required in order to determine if the weaker treatment effects for women are a consequence of the lower levels of competitiveness, or some other factor.…”
Section: Resultsmentioning
confidence: 99%
“…This approach was taken in Berge et al (2014); they find that females have weaker results from receiving capital and training, and that women were less competitive at endline. In associated work, the authors find that competitiveness as measured in their game does predict business success (Berge et al, 2015). Further research on this is required in order to determine if the weaker treatment effects for women are a consequence of the lower levels of competitiveness, or some other factor.…”
Section: Resultsmentioning
confidence: 99%
“…This paper is related to the growing literature relating attitudes towards competition to gender differences in labor market outcomes (e.g., Zhang, 2013;Buser, Niederle, and Oosterbeek, 2014;Flory, Leibbrandt, and List, 2014;Berge et al, 2015;Kamas and Preston, 2015;Reuben, Wiswall, and Zafar, 2015) and more generally with studies linking traits measured in laboratory settings with actual behavior in the field (e.g., Karlan, 2005;Ashraf, Karlan, and Yin, 2006;Benz and Meier, 2008;Fehr and Leibbrandt, 2011). These studies establish the external validity of the taste for competition traits measured developed by Niederle and Vesterlund (2007), but more importantly, they demonstrate that relevance of taste for competition as a determinant of labor market outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Buser et al (2014) show that competing in an experiment predicts the study choices of Dutch high-school students. Other studies have found correlations with the choice of entering a highly competitive university entrance exam in China (Zhang, 2013), starting salary and industry choice of graduating MBA students (Reuben et al, 2015), as well as future salary expectations of undergraduate students (Reuben et al, 2016), the investment choices of Tanzanian entrepreneurs (Berge et al, 2015) and monthly earnings in a diverse sample of the Dutch population (Buser et al, 2015).…”
Section: Literaturementioning
confidence: 99%